Effects of glibenclamide and troxerutin on the sperm parameters and histopathological changes of testis in streptozotocin-induced diabetic male rats: An experimental study - Aynaz Shokri; Bagher Pourheydar; Gholam Hossein Farjah; Mojtaba Krimipour; Maryam Pourheydar (Shahid Sadoughi University of Medical Sciences, 2023)
Abstract Background: Oxidative stress is a major contributor to diabetes mellitus (DM), which leads to testicular damage and infertility. Objective: The aim of this study was to investigate the effects of glibenclamide (GL) as a chemical medicine and troxerutin (TR) as an herbal agent on sperm parameters and histopathological changes of testis in diabetic male rats. Materials and Methods: Forty male Wistar rats (230-260 gr) were randomly divided into 5 groups (n = 8/each), including control, diabetic (D), GL, TR, and GL+TR. DM was induced by the administration of 60 mg/kg streptozotocin intraperitoneally. The groups were treated with 5 mg/kg/day of GL or 150 mg/kg/day of TR via oral gavage for 4 wk. In the final stage of the treatment, blood sampling was done for biochemical analysis. The rats were then sacrificed and their left testis and epididymis were dissected for sperm analysis, histopathology, and morphometric assessment. Results: A significant decrease in the number, motility, viability, maturity, and chromatin quality of sperm was found in diabetic rats compared to control group. (p < 0.001). DM also increased the malondialdehyde level and decreased the level of the serum's total antioxidant capacity compared to the control group (p < 0.001). Furthermore, we observed a significant difference in seminiferous tubule diameter, germinal epithelium height, and testicular histological abnormalities in diabetic rats compared to control group (p < 0.001). Administration of GL, TR, and their combination improved the above-mentioned parameters, and treatment with TR provided a higher improvement (p < 0.001). Conclusion: According to these findings, it can be concluded that TR plays a more influential role than GL to treat diabetic-induced infertility.